2016
DOI: 10.1016/j.bios.2016.07.112
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent imaging of Au3+ in living cells with two new high selective Au3+ probes

Abstract: Two new acetylenic compounds were designed and synthesized as the probes to realize the detection and recognition of Au(3+). The latent fluorophores was rearranged into the fluorescent coumarin derivatives with strong fluorescence by a gold ion-mediated hydroarylation reaction. In the meanwhile, the generated fluorescent substances were also isolated and characterized. The probes identified Au(3+) ions highly selectively over other biologically relevant metal ions, and detection concentration of Au(3+) was as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Gold is an important noble metal and its compounds are extensively used as catalytic agents, pharmaceuticals, and in the electronic industry. In its cationic form, gold has also been demonstrated to be harmful to the nervous system, kidneys, and liver. , …”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Meta...mentioning
confidence: 99%
See 2 more Smart Citations
“…Gold is an important noble metal and its compounds are extensively used as catalytic agents, pharmaceuticals, and in the electronic industry. In its cationic form, gold has also been demonstrated to be harmful to the nervous system, kidneys, and liver. , …”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Meta...mentioning
confidence: 99%
“…Yin’s group developed two acetylenic compounds 185 and 186 (Figure ) as fluorescent chemosensors for Au 3+ . These fluorogenic sensors require the presence of Au 3+ to enable an in situ hydroarylation reaction, resulting in the formation of a coumarin.…”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Meta...mentioning
confidence: 99%
See 1 more Smart Citation
“…3B ). 42 Acetylene compounds were utilized as probes to rearrange potential fluorophores into fluorescent coumarin derivatives, which could realize the detection and recognition of Au 3+ via a gold ion-mediated hydro-arylation reaction. The experimental results showed that these two probes have good selectivity and sensitivity for the detection of gold ions, and their detection limit was as low as 0.1 nM.…”
Section: Rational Design Of Covalent Assembly-based Fluorescent Probesmentioning
confidence: 99%
“…In some cases, we also classify oxidative conditions using biologically less relevant pH values into class C. In the model systems class B and C, three subgroups can be distinguished: (a) oxygen atom donors (H2O2, t-BuOOH, O2 in alkaline media) (Costa et al, 2021;Wenz et al, 2019) (b) electron donors (e.g. NaIO4, K3Fe(CN)6, Ru 3+ , Cu 2+ , Fe 2+ /Fe 3+ , Au 3+ ) (Galletti et al, 2018;Pradhan et al, 2020;Wu et al, 2021;Yang et al, 2016) (c) agents that mimic the nitrating capacity of peroxynitrite (eg. NaNO2) (Ozyurt & Otles, 2020;Vossen & De Smet, 2015).…”
Section: Biomimetic Oxidative Chemistry -Exploring the Scavengomementioning
confidence: 99%

Scavengome of an Antioxidant

Hunyadi,
Agbadua,
Takáts
et al. 2022
Preprint